If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -3 = 3a + 4 Reorder the terms: -3 + 4a = 3a + 4 Reorder the terms: -3 + 4a = 4 + 3a Solving -3 + 4a = 4 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -3 + 4a + -3a = 4 + 3a + -3a Combine like terms: 4a + -3a = 1a -3 + 1a = 4 + 3a + -3a Combine like terms: 3a + -3a = 0 -3 + 1a = 4 + 0 -3 + 1a = 4 Add '3' to each side of the equation. -3 + 3 + 1a = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 1a = 4 + 3 1a = 4 + 3 Combine like terms: 4 + 3 = 7 1a = 7 Divide each side by '1'. a = 7 Simplifying a = 7
| 26*34=5x | | 2*34=x | | 2*34= | | X^2+12x=-40 | | 4(2x+1)-7=6+5 | | 0.5x^2-3x=2 | | 7(15+6a)=486 | | 21(15+6a)=486 | | 21x(15+6a)=486 | | 5(4x-3)+8=-2 | | 2(x+3)=5(2-x)-2 | | (x-2)+4=6x-17 | | B=P(500-20P)-C(500-20P) | | q=500-20P | | 2x+x=51 | | 2x+6=10-5x-2 | | 34+x=-13 | | 5(x+5)= | | 2b=25-3b | | -14d-16=2(d+8)-12d | | 24d+20=116 | | 5(b+2)=8b-11 | | 0.5x+3=-x | | 3(x+6)+103=8x-5(x-5) | | -13d-21=3(d+7)-10 | | 13x+5(x+1)=18(x+1)-13 | | 3-9x=5x-4 | | 4x+x+1=6 | | 3x^2-(2k-3)x-2k=0 | | 5.68-4.61x-1.9x=23.908 | | 7+9+b=40 | | -7x=-26+6x |